PENGARUH PENERAPAN MEDIA PEMBELAJARAN IPA BERBASIS 3D TERHADAP HASIL BELAJAR SISWA KELAS V SD - Septiana, Nanda; Nur Fadhilah, Mutik (Al-Adawat : Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
The study aim to describe the effect of implementating 3D based sicence learning media on the laerning outcames of fifth grade elementary school students. The research method used is, experimental with a one group pretest-postest only design. The population in this study consisted of all elementary school students residing in Toronan, with fifth grade students selected as the sample using random sampling. The research instrument was a learning outcome test, anda data were analyzed using a t-test to measure the significance pf the impact. The result showed that 3D media had a significant effect pn improving students learning outcomes in science subjects, with a significance value of 0,000<0,05. This media helps students understand  abstract concepts more concretely, enchancing comprehension and is recommended as an affective alternative in science learning for fifth grade classes